An Apoptosis-Related Gene Prognostic Index for Colon Cancer - Tang, Hanmin; Wang, Jing; Luo, Xuehui; Wang, Qi; Chen, Jie; Zhang, Xinyue; Li, Qiuting; Gao, Chengyi; Li, Yuesen; Han, Suxia (Frontiers in Cell and Developmental Biology, 2021)
Purpose: To construct the apoptosis related gene prognostic index (ARGPI) of colon cancer, clarify the molecular and immune characteristics of the risk subgroup defined by the prognostic index and the benefits of adjuvant chemotherapy. Integrating the prognostic index and clinicopathological risk factors to better evaluate the prognosis of patients with colon cancer. Methods: Based on the colon adenocarcinoma data in TCGA database, 20 apoptosis related hub genes were screened by weighted gene co-expression network analysis (WGCNA). Five genes constituting the prognosis model were determined by Cox regression method and verified by Gene Expression Omnibus (GEO) dataset. Then, the molecular and immune characteristics of risk subgroups defined by the prognostic index and the benefits of adjuvant chemotherapy were analyzed. Finally, The Nomograms integrating ARGPI and four clinicopathological risk factors was used to evaluate the prognosis of patients with colon cancer. Results: The ARGPI was constructed based on FAS, VWA5A, SPTBN2, PCK1 and TIMP1 genes. In the TCGA cohort, patients in the low-risk subgroup had a longer progression free interval (PFI) than patients in the high-risk subgroup, which was consistent with the results in the GEO cohort. The comprehensive results showed that the high-risk score was related to the enrichment of cell cycle pathway, high mutation rate of TP53 and KRAS, high infiltration of T cells regulatory (Tregs), immunosuppressive state and less benefit of chemotherapy. On the contrary, low-risk score is related to drug metabolism related pathways, low TP53 and KRAS mutation rate, high infiltration of plasma cells, T cells CD4 memory resting and eosinophils, active immune function, and benefit more from chemotherapy. Receiver operating characteristic curve (ROC) of 2-year progress prediction evaluation showed that ARGPI had higher prognostic accuracy than TNM staging. The Nomograms integrating ARGPI and clinicopathological risk factors can better evaluate the prognosis of patients with colon cancer. Conclusions: Apoptosis associated gene prognostic index (ARGPI) is a promising biomarker to identify the risk of colon cancer progression, molecular and immune characteristics and the benefit of chemotherapy. This is a reliable method to predict the prognosis of patients with colon cancer. It can help doctors formulate more effective treatment strategies.